Gastrosophy today: can Charles Fourier's vision of food become a model for 21st century food empowerment projects? - Fleurot, Magali (Cadernos de Literatura Comparada (teste), 2017)
French utopian writer Charles Fourier coined the word gastrosophy to describe a science which would merge gastronomy, cooking, agriculture and preserving food. Fourier’s goal, contrary to what was generally being done in the 19th century, was not so much to feed the poor but to reach a certain equality before food: the poor man would not eat as much but as well as the rich man. However, when his followers found ways to put his ideas into practice they encountered very practical problems which quickly led to an emphasis on the sole agricultural side of gastrosophy, leaving aside the other elements. Nevertheless, it is interesting to note that Fourier’s ideas resonate today in what happens both in France and in Great Britain where the same issues (adulterated food, tasteless and standardized vegetables) bring forth the same answer as what Fourier had proposed in many ways. I will try and form a picture of Fourier’s ideas on gastrosophy and more specifically on the education to taste. I will also attempt to introduce the movements which seem to be the most representative gastrosophist endeavours emerging in the 21st century. My last demonstration will discuss the political implications of gastrosophy today particularly as far as food justice is concerned when inequalities as far as access to healthy food are far from being bridged